Preparation of Ti/TiO2-PANi electrodes by combining method of thermal treatment with polymerization processing and their electrochemical property - Xuan, Mai Thi; Duyen, Nguyen The; Tot, Pham Thi; Thanh Thuy, Mai Thi; Van Anh, Nguyen Thi; Binh, Phan Thi (Vietnam Journal of Chemistry, 2016)
Ti/TiO2-PANi-electrodes were synthesized by combining method of thermal treatment of titanium substrate with chemical polymerization processing of aniline on which. Their morphological structure was observed by scanning electron microscopy. The presence of PANi and TiO2 were indicated by infrared spectra and X-ray diffraction, respectively. Their electrochemical properties were characterized by cyclic voltammetry and impedance spectroscopy. The results showed that their photoelectrochemical property with light on in 0.5 M H2SO4 indicating a n-conductor that depended on PANi thickness covered TiO2-layer among them the best one obtained by oxidative temperature of 500 oC for 30 minutes during thermal treatment of titanium substrate connected with an immersing into acidic aniline solution for only 8 min during polymerization